Genetic characterizations of Giardia duodenalis in sheep and goats in Heilongjiang Province, China and possibility of zoonotic transmission. - Weizhe Zhang; Xiaoli Zhang; Rongjun Wang; Aiqin Liu; Yujuan Shen; Hong Ling; Jianping Cao; Fengkun Yang; Xiaoyun Zhang; Longxian Zhang (Public Library of Science (PLoS), 2012)
BACKGROUND: Giardia duodenalis is a widespread intestinal protozoan of both humans and mammals. To date, few epidemiological studies have assessed the potential and importance of zoonotic transmission; and the human giardiasis burden attributable to G. duodenalis of animal origin is unclear. No information about occurrence and genotyping data of sheep and goat giardiasis is available in China. The aim of the present study was to determine prevalence and distribution of G. duodenalis in sheep and goats in Heilongjiang Province, China, and to characterize G. duodenalis isolates and assess the possibility of zoonotic transmission. METHODOLOGY/PRINCIPAL FINDINGS: A total of 678 fecal specimens were collected from sheep and goats on six farms ranging in age from one month to four years in Heilongjiang Province, China. The average prevalence of G. duodenalis infection was 5.0% (34/678) by microscopy after Lugol's iodine staining, with 5.6% (30/539) for the sheep versus 2.9% (4/139) for the goats. Molecular analysis was conducted on 34 G. duodenalis isolates based on the triosephosphate isomerase (tpi) gene. 29 tpi gene sequences were successfully obtained and identified as assemblages A (n = 4), B (n = 2) and E (n = 23). High heterogeneity was observed within assemblage E at the tpi locus, with five novel subtypes found out of seven subtypes. Two subtypes of assemblage A were detected, including subtype AI (n = 3) and a novel subtype (designated as subtype AIV) (n = 1). Two assemblage B isolates were identical to each other in the tpi gene sequences. CONCLUSIONS/SIGNIFICANCE: This is the first report of G. duodenalis infections in sheep and goats in China. The present data revealed the unique endemicity on prevalence, distribution and genetic characterization of G. duodenalis in sheep and goats in Heilongjiang Province. The findings of assemblages A and B in sheep and goats implied the potential of zoonotic transmission.